STUDIES ON GENETIC DIVERSITY AMONG ALTERNARIA BLIGHT TOLERANT INDIAN MUSTARD GENOTYPES USING SSR MARKERS - CHANDRA, VISALAKSHI; PANT, USHA; BHAJAN , RAM; A. K. SINGH, (The Bioscan, 2013)
Brassica species represents one of the most important oilseed crops in India; nevertheless their genetic diversity is still to be studied. An understanding of genetic diversity is essential for proper utilization of genotypes in the target oriented research programmes. 37 diverse Indian mustard genotypes including recombinant lines, indigenous lines, exotic lines with Alternaria blight tolerant (PAB 9511) and susceptible check (Varuna) were utilized. Ten A and C genome specific SSR markers were used for the development of molecular profile. A total of 41 bands were amplified that exhibited 97.56% polymorphism. Genotypes were grouped into 5 clusters. Presence of unique band helped in the identification of specific genotype. PAB-09-1, PAB-05-16, PAB 09-11, PAB-09-9, EC 399312 and EC399301shared common cluster with PAB 9511 and were at par in their disease score index to PAB 9511 as well. So these primers after validation can be used as maker for Alternaria bilght screening.